2014
DOI: 10.1093/eurheartj/eht545
|View full text |Cite
|
Sign up to set email alerts
|

Bioresorbable vascular scaffolds in acute ST-segment elevation myocardial infarction: a prospective multicentre study 'Prague 19'

Abstract: AimsBioresorbable vascular scaffolds (BVSs) have been studied in chronic coronary artery disease, but not in acute ST-segment elevation myocardial infarction (STEMI). This prospective multicentre study analysed the feasibility and safety of BVS implantation during primary percutaneous coronary intervention (p-PCI) in STEMI.Methods and resultsBioresorbable vascular scaffold implantation became the default strategy for all consecutive STEMI patients between 15 December 2012 and 30 August 2013. A total of 142 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
1
5

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(85 citation statements)
references
References 18 publications
3
76
1
5
Order By: Relevance
“…Distal embolization occurred only in 1 (4.3%) case and no-reflow phenomenon in none. These findings are in line with recently published studies in STEMI population treated with the same type of BVS [15,16].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Distal embolization occurred only in 1 (4.3%) case and no-reflow phenomenon in none. These findings are in line with recently published studies in STEMI population treated with the same type of BVS [15,16].…”
Section: Discussionsupporting
confidence: 93%
“…Success rates were defined as in previous studies with BVS implantation [15,16]. Device success was described as the presence of residual diameter stenosis < 30% of the segment of the culprit lesion, covered by the BVS, assessed by angiographic visual estimation.…”
Section: Coronary Angiography and Oct Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from available observational studies and randomized clinical trials are reassuring and very promising (16)(17)(18)(19)(20)(21)(22)(23). Rates of early BVS thrombosis in adverse anatomic scenarios, including the presence of a highly thrombogenic milieu, however, appear to be not negligible.…”
Section: Discussionmentioning
confidence: 99%
“…The everolimus-eluting bioresorbable vascular scaffolds for treatment of patients presenting with ST-segment elevation myocardial infarction (BVS STEMI) study was the first that evaluated BRS use in STEMI (103 The investigators reported good procedural and clinical outcome in these patients, but with stent thrombosis rate of 2.4%, higher than that seen in clinical trials (106). An excellent review of BRS use in STEMI has been published elsewhere (107) and the authors stated that the unique properties of the BRS make STEMI the ideal scenario for BRS implantation.…”
Section: Brs Use In Stemi Patientsmentioning
confidence: 99%